PEMANFAATAN IKAN BANDENG (Chanos chanos) MENJADI PRODUK BERNILAI EKONOMIS TINGGI DI DESA BONTO BAHARI KEC. BONTOA KAB. MAROS - Kasmawati, Kasmawati; Hasrun, Hasrun; Ernaningsih, Ernaningsih; Hamsiah, Hamsiah (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, 2022)
Bonto Bahari Village, Maros Sul-Sel Regency is one of the milkfish producing areas The main problem faced by this village is that when harvest time comes, milkfish commodities are abundant so that their selling value decreases and even causes losses to pond farmers. Laskar Jaya Bahari farmer group together with the community partnership program team from the Indonesian Muslim University (UMI) are looking for solutions to the problems mentioned above, so the efforts made are the Utilization of Milkfish (Chanos Chanos) into High Economic Value Products. Community service activities were carried out on September 28, 2020 in sabanga hamlet, Bonto Bahari Village, Bontoa Regency, Maros Regency with group partner